Source location and evolution of a multilane type II radio burst - Zucca, P; Zhang, P; Kozarev, K; Nedal, M; Dey, S; Mancini, M; Kumari, A; Morosan, DE; Dabrowski, B; Gallagher, PT; Krankowski, A; Vocks, C (EDP SCIENCES S A, 2026)
Context. Shocks in the solar corona are capable of accelerating electrons that in turn generate radio emission known as type II radio bursts. The characteristics and morphology of these radio bursts in the dynamic spectrum reflect the evolution of the shock itself, together with the properties of the local corona where the shock propagates.
Aims. In this work we study the evolution of a complex type II radio burst with a multilane structure to find the locations where the radio emission is produced and relate them to the properties of the local environment where the shock propagates.
Methods. Using radio imaging, we were able to separately track each lane composing the type II burst and relate the position of the emission to the properties of the ambient medium, such as density, Alfv & eacute;n speed, and magnetic field.
Results. We show that the radio burst morphology in the dynamic spectrum changes with time and is related to the complexity of the local environment. The initial stage of the radio emission is characterized by a single broad lane in the spectrum, while the later stages of the radio signature evolve in a multilane scenario. The radio imaging reveals how the initial stage of the radio emission separates with time into different locations along the shock front as the density and orientation of the magnetic field change along the shock propagation. At the time when the spectrum shows a multilane shape, we find a clear separation of the imaged radio sources propagating in regions with different densities.
Conclusions. By combining radio imaging with the properties of the local corona, we describe the evolution of a type II radio burst and, for the first time, identify three distinct radio emission regions above the coronal mass ejection front. Two regions were located at the flanks, producing earlier radio emission than the central position, in accordance with the complexity of density and Alfv & eacute;n speed values in the regions where radio emission is generated. This unprecedented observation of a triple-source structure provides new insights into the nature of multilane type II bursts.